Not Only High Number and Specific Comorbidities but Also Age Are Closely Related to Progression and Poor Prognosis in Patients With COVID-19 - Liu, Dafeng; Zheng, Yongli; Kang, Jun; Wang, Dongmei; Bai, Lang; Mao, Yi; Zha, Guifang; Tang, Hong; Zhang, Renqing (Frontiers in Medicine, 2022)
Background— Some patients with comorbidities and rapid disease progression have a poor prognosis. Aim—We aimed to investigate the characteristics of comorbidities and their relationship with disease progression and outcomes of COVID-19 patients. Methods— A total of 718 COVID-19 patients were divided into five clinical type groups and eight age-interval groups. The characteristics of comorbidities were compared between the different clinical type groups and between the different age-interval groups, and their relationships with disease progression and outcomes of COVID-19 patients were assessed. Results—Approximately 91.23% (655/718) of COVID-19 patients were younger than sixty years old. Approximately 64.76% (465/718) had one or more comorbidities, and common comorbidities included non-alcoholic fatty liver disease (NAFLD), hyperlipidaemia, hypertension, diabetes mellitus (DM), chronic hepatitis B (CHB), hyperuricaemia and gout. COVID-19 patients with comorbidities were older, especially those with chronic obstructive pulmonary disease (COPD) and cardiovascular disease (CVD). Hypertension, DM, COPD, chronic kidney disease (CKD) and CVD were mainly found in severe COVID-19 patients. According to spearman correlation analysis the number of comorbidities was correlated positively with disease severity, the number of comorbidities and NAFLD were correlated positively with virus negative conversion time, hypertension, CKD and CVD were primarily associated with those who died, and the above-mentioned correlation existed independently of age. Risk factors included age, the number of comorbidities and hyperlipidaemia for disease severity, the number of comorbidities, hyperlipidaemia, NAFLD and COPD for the virus negative conversion time, and the number of comorbidities and CKD for prognosis. Number of comorbidities and age played a predictive role in disease progression and outcomes. Conclusions—High number and specific comorbidities except age are closely related to progression and poor prognosis in patients with COVID-19. These findings provide a reference for clinicians to focus on the number and specific comorbidities in COVID-19 patients to predict disease progression and prognosis.